Outdoor Massive MIMO Testbed With Directional Beams: Design, Implementation, and Validation - Spandan Bisoyi; Pasupuleti Muralimohan; Harish Kumar Dureppagari; Pavan Reddy Manne; Kiran Kuchi (IEEE Access)
Massive MIMO has emerged as a key technology for the deployment of 5G networks, significantly enhancing network capacities. By simultaneously scheduling multiple users on the same time and frequency resources, substantial improvements in network capacity and spectral efficiency can be achieved. However, various bottlenecks in deployments, such as limited antenna directivity, interference from neighboring sectors, and power division among scheduled layers, restrict the achievable number of paired users, ultimately limiting network capacity. Current deployments demonstrate around $8-16$ user pairings in downlink using 64 antenna ports (128 antenna elements) in a 120° sector by utilizing multiuser MIMO techniques. In this work, we study the achievable multiuser MIMO gains in an outdoor environment by deploying narrow directional beams using a rectangular antenna structure having 48 antenna ports (192 antenna elements), each port with a beamwidth of 30° in azimuth and 90° in elevation. By leveraging this two-dimensional structure, we explore the two dimensions to identify spatially uncorrelated users for pairing. Through extensive outdoor evaluations using the testbed, we demonstrate the capability of pairing up to 10 users simultaneously within the 30° sector using QPSK modulation scheme. Furthermore, our analysis of normalized pairing opportunities for all users revealed an unequal distribution of pairing opportunities among different users. To address this, we introduced a fair scheduling algorithm alongside user pairing, which reduces the simultaneous number of paired users to 7 with QPSK modulation within the 30° sector, ensuring equal pairing opportunities for all users. Additionally, to support higher modulation scheme we modified the correlation threshold and achieved a pairing of 4 users with 16QAM modulation, and 3 users with 64QAM modulation scheme. Our experimental results indicate that the use of fixed directional beams to offer 360° coverage using a set of antenna panels results in substantial multiuser MIMO gains compared to existing 5G multiuser MIMO methods. All our findings are supported by comprehensive experimental analyses detailed in this paper.